CRL4AMBRA1 targets Elongin C for ubiquitination and degradation to modulate CRL5 signaling. (30th August 2018) - Chen, Si‐Han; Jang, Gwendolyn M; Hüttenhain, Ruth; Gordon, David E; Du, Dan; Newton, Billy W; Johnson, Jeffrey R; Hiatt, Joseph; Hultquist, Judd F; Johnson, Tasha L; Liu, Yi‐Liang; Burton, Lily A; et al.
Abstract: Multi‐subunit cullin‐RING ligases (CRLs) are the largest family of ubiquitin E3 ligases in humans. CRL activity is tightly regulated to prevent unintended substrate degradation or autocatalytic degradation of CRL subunits. Using a proteomics strategy, we discovered that CRL4 AMBRA 1 (CRL substrate receptor denoted in superscript) targets Elongin C (ELOC), the essential adapter protein of CRL5 complexes, for polyubiquitination and degradation. We showed that the ubiquitin ligase function of CRL4 AMBRA 1 is required to disrupt the assembly and attenuate the ligase activity of human CRL5 SOCS 3 and HIV‐1 CRL5 VIF complexes as AMBRA1 depletion leads to hyperactivation of both CRL5 complexes. Moreover, CRL4 AMBRA 1 modulates interleukin‐6/STAT3 signaling and HIV‐1 infectivity that are regulated by CRL5 SOCS 3 and CRL5 VIF, respectively. Thus, by discovering a substrate of CRL4 AMBRA 1, ELOC, the shared adapter of CRL5 ubiquitin ligases, we uncovered a novel CRL cross‐regulation pathway. Synopsis: The ubiquitin E3 ligase CRL4 AMBRA 1 targets Elongin C (ELOC), the shared adapter of CRL5 ubiquitin ligases, for polyubiquitination and degradation, thereby modulating IL‐6/STAT3 signaling and HIV‐1 infectivity that are regulated by CRL5 SOCS 3 and HIV‐1 CRL5 VIF, respectively. Quantitative proteomics identifies ELOC as a novel substrate of CRL4 AMBRA1 . ELOC mediates the interaction between AMBRA1 and multiple CRL5 substrate receptors. ELOC targeting by CRL4 AMBRA1 attenuates the ligase activity of CRL5 SOCS3 and HIV‐1 CRL5 VIF . CRL4 AMBRA1 modulates CRL5 SOCS3 ‐ and HIV‐1 CRL5 VIF ‐regulated functions. Abstract : Proteomic identification of the Cul5 ubiquitin ligase adaptor Elongin C as AMBRA1‐binding substrate of Cul4 ligase exemplifies crosstalk between cullin‐RING E3s that can modulate both cytokine signaling and HIV‐1 infectivity.